Local sediment and lime but no straw amendments can potentially improve barley biomass and yield at the field plot scale in Kenya - Scherwietes, Eric; Six, Johan; Bawen, Titus Kiplagat; Schaller, Jörg (Frontiers in Environmental Science, 2025)
Soil acidification and nutrient leaching are major agricultural challenges in East Africa, leading to aluminum (Al) toxicity and poor crop yields. Various soil amendments are used worldwide to increase soil pH and crop production. Local sediment amendments have been identified as a potential soil improvement in Kenya, but the mechanisms remain unclear. This study examined the effects of liming, straw return, and local sediment amendments on nutrient availability and barley yield in Eldoret, Kenya. Plots were established with 1% and 3% of two local sediments (from Baringo and Nakuru) or with 0.15% lime, each with and without straw addition. Baringo 3% and lime treatments significantly reduced soil Al availability and increased soil pH, soil phosphorous (P) availability and barley yield (Baringo 3%: 1.3 t ha-1, Lime: 0.91 t ha-1), while the control had no yield. However, only Baringo 3% also increased soil silicon (Si) availability, achieving the highest yield. Other treatments and straw return had no significant impact on nutrient availability and plant production. These results indicate that the increase in barley yield with local sediment may be driven mainly by carbonate dissolution raising soil pH, while higher Si availability and accumulation could further enhance plant production. However, the beneficial effects are dependent on the sediment material and amendment rate.